Gene Regulation of Biofilm-Associated Functional Amyloids - Khushal Khambhati; Jaykumar Patel; Vijaylaxmi Saxena; Parvathy A; Neha Jain (Pathogens, 2021)
Biofilms are bacterial communities encased in a rigid yet dynamic extracellular matrix. The sociobiology of bacterial communities within a biofilm is astonishing, with environmental factors playing a crucial role in determining the switch from planktonic to a sessile form of life. The mechanism of biofilm biogenesis is an intriguingly complex phenomenon governed by the tight regulation of expression of various biofilm-matrix components. One of the major constituents of the biofilm matrix is proteinaceous polymers called amyloids. Since the discovery, the significance of biofilm-associated amyloids in adhesion, aggregation, protection, and infection development has been much appreciated. The amyloid expression and assembly is regulated spatio-temporarily within the bacterial cells to perform a diverse function. This review provides a comprehensive account of the genetic regulation associated with the expression of amyloids in bacteria. The stringent control ensures optimal utilization of amyloid scaffold during biofilm biogenesis. We conclude the review by summarizing environmental factors influencing the expression and regulation of amyloids.